Effects of vermicompost and phosphatic fertilizers on soybean yield, phosphorus content, uptake, and post-harvest soil properties - M. Abdullah Al Mamun; Jannatul Tamanna; Md. Rayhanul Hoque; A.K.M. Mosharof Hossain; Hiroshi Hasegawa (Universitas Sebelas Maret, 2025)
To boost phosphorus (P) availability in soils, adding organic matter like compost, manure, or vermicompost (VC) is a sustainable solution. A field experiment investigated how VC and phosphatic fertilizers affect P bioavailability, plant uptake, and yield response of BARI Soybean-5. Eight treatments i.e., T1 = control (no P), T2 = 100% recommended dose of P (RDP) from triple superphosphate (TSP), T3 = 100% RDP from diammonium phosphate (DAP), T4 = 100% RDP from VC, T5 = 75% RDP from TSP + 25% from VC, T6 = 75% RDP from DAP + 25% from VC, T7 = 50% RDP from TSP + 50% from VC, and T8 = 50% RDP from DAP + 50% from VC were replicated thrice on randomized complete block design (RCBD). T2 treatment generated a maximum seed yield of soybean (1.66 t ha-1), exceeding T3, T5, T6, T7, and T8 treatments with 1.63, 1.54, 1.52, 1.50, and 1.50 t ha-1, respectively. Also, T2 performed the highest P contents in seed, root, and straw (1.27, 0.19, and 0.41%, respectively) and total uptake of P (28.15 kg ha-1) among the treatments. T4 exhibited significantly higher levels of organic C, total N, available P, exchangeable K, and available S. Overall findings revealed that growing BARI Soybean-5 with 100% RDP from TSP (T2) proved a good practice for yield response, but 100% RDP from VC (T4) would be preferable for long-term soil health. This study would be helpful for choosing organic or inorganic sources of P fertilizers for soybean production.